Himalayan art resources (1997)
[Dt.:] Himalaya Art Resources ist eine umfassende Datenbank für Kunst aus Tibet und der Himalaja-Region. Die Sammlungen verschiedener Museen, Universitäten oder auch sonstiger Einrichtungen und Personen über diese Datenbank verfügbar gemacht. Des Weiteren werden verschiedene Arten von Kunstobjekte aus der Himalaja-Regionen klassifiziert und katalogisiert. - [Engl.:] The mission of the Himalayan Art Resources is to create a comprehensive research database, a virtual museum, of Himalayan and Tibetan art: Firstly, the Website exhibits images of art from museum, university and private collections around the world. Secondly, the Website catalogs all Himalayan art objects that are known through past or present collections or publications. The database identifies and catalogues paintings, sculpture, prints, initiation cards and murals. When a digital image of an object is not available, the database uses a placeholder image. Book cover images are used for publications and generic placeholders for collections.